EFL pre-service teachers’ beliefs about peer coaching as a tool for their professional development - Valladarez Cueva, Naomy Elizabeth (2024)
Peer coaching has appeared as a powerful tool in EFL pre-service teachers’ preparation, offering a collaborative platform to refine instructional strategies and fostering a culture of continuous improvement in the journey towards teaching excellence. Despite its acknowledged importance, according to the researcher’s observations, innovative approaches such as peer coaching remain underutilized in university internship programs for prospective teachers. Likewise, there is a lack of research exploring how these future educators perceive the approach. Given this context, the present study looked to describe EFL pre-service teachers’ beliefs about peer coaching as a tool to enhance their professional development, exploring strengths and barriers. In pursuit of this aim, an explanatory sequential mixed method was employed. A purposive sample of twenty-five novice teachers was selected, all of whom participated in the peer coaching program, which was conducted during their seventh semester in the period of October 2023 - March 2024, as part of their practicum in various municipal institutions located in the city of Loja, Ecuador. Questionnaires, serving as the quantitative instrument, were administered to all twenty-five participants, and the collected data was analyzed using descriptive statistics. Additionally, semi-structured interviews, serving as the qualitative instrument, were conducted with six participants, and were analyzed using thematic analysis. The findings showed that peer coaching is seen as a highly effective method for improving teaching skills and professional capabilities by offering opportunities for knowledge sharing, mutual learning, and reflective practice, thereby fostering continuous improvement and professional growth. However, further research with more diverse samples is necessary to confirm these findings and provide a more comprehensive understanding of peer coaching's impact. Key Words – novice teachers training programs, collaborative learning, teaching skills, feedback